Mafias y tráficos ilícitos: El narcotráfico gallego - Moreno Oliver, Francesco Xavier (Quadernos de criminología, 2021)
Galician drug trafficking clans in Spain are a model of local organized crime, which currently works in coordination with different international mafias. Its origins go back to the estraperlo of the fif'ties. Subsequently, they specialized in tobacco smuggling, creating an important logistics infrastructure that in the early 1980's adapted for drug trafficking.